MATHEMATICAL MODELING ON ASSESSING COVID-19 VACCINATION STRATEGY: IN CONTEXT OF REGIONS IN INDONESIA - Khairudin Sukandar, Kamal
As a mitigation measure for the COVID-19 outbreak in Indonesia, this study assesses several strategies for implementing vaccination in Indonesia. There are four things that are studied in this research: the effect of the vaccination timeline, the effect targeting certain age group for jab, the effect of vaccination distribution, and the effect of the massive mobility, especially for Mudik Lebaran 2021. In practice, the compartmental model SIQRD (Susceptible , Infected, Quarantined , Recovered, Death) is built by accommodating reinfection, infection, and even vaccination factors. As a development, the SIQRD model was developed based on each issue: adding the age structure for addressing the age group target issue, and adding mobility factors for addressing the massive mobility effect.